THE IMPORTANCE OF COLOR IN ORGANIZING THE IDEOLOGICAL DIRECTION IN MODERN UZBEK PROSE (Scientific journal of the Fergana State University, 2023)
In this article, the question of the meaning of color in the organization of the ideological orientation in modern Uzbek prose is considered on the example of Shoim Butaev's story "Black Fog".In the course of the research, historical-literary, genetic, comparative-historical, artistic analysis, description methods are used. In the plot of the story, four episodes are interconnected by means of black. The fact that the fate of the hero “represented” by the author will occur through a connection with the color expression of the area indicates the inevitability of a tragic fate. Through accentuation, it is more firmly fixed in the imagination: the repeated, emphasized use of black in its combinations, as a leitmotif, becomes an omen of further tragic scenes. The symbolic-negative expression of black is reflected in the psychological drama. In the work, black is not only a negative expression, but also a positive symbol. Also, two different concepts in the black symbol move parallel to the contradictions in the hero‘s psyche. In the story, color is an important factor that forms the ideological logic of the writer, in which the symbolic expression of color in its own way moves the images and details of the work in the artistic space.